On the road with Saint Augustine : a real-world spirituality for restless hearts - Smith, James K. A., 1970- (Grand Rapids,MI Brazos Press, 2019)
This is not a book about Saint Augustine. In a way, it's a book Augustine has written about each of us. Popular speaker and award-winning author James K. A. Smith has spent time on the road with Augustine, and he invites us to take this journey too, for this ancient African thinker knows far more about us than we might expect. Following Smith's successful You Are What You Love, this book shows how Augustine can be a pilgrim guide to a spirituality that meets the complicated world we live in. Augustine, says Smith, is the patron saint of restless hearts--a guide who has been there, asked our questions, and knows our frustrations and failed pursuits. Augustine spent a lifetime searching for his heart's true home and he can help us find our way. "What makes Augustine a guide worth considering," says Smith, "is that he knows where home is, where rest can be found, what peace feels like, even if it is sometimes ephemeral and elusive along the way." Addressing believers and skeptics alike, this book shows how Augustine's timeless wisdom speaks to the worries and struggles of contemporary life, covering topics such as ambition, sex, friendship, freedom, parenthood, and death. As Smith vividly and colorfully brings Augustine to life for 21st-century readers, he also offers a fresh articulation of Christianity that speaks to our deepest hungers, fears, and hopes.
Orientation : -- Heart on the run: how to hit the road -- Augustine our contemporary : how to find yourself -- A refugee spirituality : how to live between -- Detours on the way to myself : -- Freedom : how to escape -- Ambition: how to aspire -- Sex : how to connect -- Mothers : how to be dependent -- Friendship : how to belong -- Enlightenment : how to believe -- Story : how to be character -- Justice : how to protest -- Fathers : how to be broken -- Death : how to hope -- Homecoming.
Includes bibliographical references (pages 227-238) and index.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Spirituality -- Christianity; Spiritual life -- Christianity; Christian life